2013
DOI: 10.1016/j.bmc.2013.01.027
|View full text |Cite
|
Sign up to set email alerts
|

α-Selective glycosylation affords mucin-related GalNAc amino acids and diketopiperazines active on Trypanosoma cruzi

Abstract: This work addresses the synthesis and biological evaluation of glycosyl diketopiperazines (DKPs) cyclo[Asp-(αGalNAc)Ser] 3 and cyclo[Asp-(αGalNAc)Thr] 4 for the development of novel anti-trypanosomal agents and Trypanosoma cruzi trans-sialidase (TcTS) inhibitors. The target compounds were synthetized by coupling reactions between glycosyl amino acids αGalNAc-Ser 7 or αGalNAc-Thr 8 and the amino acid (O-tBu)-Asp 17, followed by one-pot deprotection-cyclisation reaction in the presence of 20% piperidine in DMF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this context, for the synthesis of the glycosylated amino acid αGalNAc‐ThrOH (Tn; 5 ), we made use of our established glycosylation method employing HgBr 2 , by which glycosylation of FmocThr benzyl ester ( 7 ) with the azido‐derived glycosyl donor αGal(OAc) 3 N 3 Cl ( 8 ; Scheme S1), unable to exhibit any neighboring group effect, afforded exclusively the α isomer αGalN 3 ‐ThrOBn ( 9 , 78 %, Scheme S1) . Subsequently, the sugar azido group of 9 was reductively acetylated by treatment with zinc powder in THF/acetic anhydride/acetic acid, and its benzyl ester group was removed by standard hydrogenolysis (H 2 , 10 % Pd‐C, 1 h), giving the αGalNAc‐ThrOH derivative 5 (60 %) to be utilized in the solid‐phase synthesis of glycopeptide 3 (Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, for the synthesis of the glycosylated amino acid αGalNAc‐ThrOH (Tn; 5 ), we made use of our established glycosylation method employing HgBr 2 , by which glycosylation of FmocThr benzyl ester ( 7 ) with the azido‐derived glycosyl donor αGal(OAc) 3 N 3 Cl ( 8 ; Scheme S1), unable to exhibit any neighboring group effect, afforded exclusively the α isomer αGalN 3 ‐ThrOBn ( 9 , 78 %, Scheme S1) . Subsequently, the sugar azido group of 9 was reductively acetylated by treatment with zinc powder in THF/acetic anhydride/acetic acid, and its benzyl ester group was removed by standard hydrogenolysis (H 2 , 10 % Pd‐C, 1 h), giving the αGalNAc‐ThrOH derivative 5 (60 %) to be utilized in the solid‐phase synthesis of glycopeptide 3 (Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, our described HgBr 2 ‐catalyzed glycosylation reaction of FmocSer benzyl ester ( 10 , Scheme ) with αGal(OAc) 3 N 3 Cl 8 led to the predicted α glycoside (50 %), along with a very low yield of βGalN 3 ‐FmocSerOBn (4 %), whereas none of the azido threonine‐derived β anomer could be obtained by glycosylation of threonine acceptor 7 with the donor 8 . Thus, the fact that glycosylation reactions utilizing the azido donor 8 were ineffective in providing either βGalNAc‐FmocSer or βGalNAc‐FmocThr prompted us to apply an alternative route involving the glycosyl donor αGal(OAc) 3 NAcCl ( 11 ), possessing an acetamide C‐2 participating group.…”
Section: Resultsmentioning
confidence: 99%
“…2.1.1. Synthesis of glycosyl amino acids : We have previously reported on the use of HgBr 2 as an effective glycosylation catalyst for the synthesis of related Ser/Thr glycosyl amino acids containing the distinct α/βGlcNAc, α/βGalNAc, or αLacNAc cores 3335. HgBr 2 ‐catalyzed glycosylations utilizing N 3 ‐derived (C‐2 non‐participating group) and NHAc‐derived (C‐2 participating group) glycosyl donors afforded, in most cases, the expected α‐glycosides (1,2‐ cis ) and β‐glycosides (1,2‐ trans ), respectively, as major products, as well as small amounts of the corresponding unexpected β‐ and α‐glycosides (which represents a broadening of the potential application of HgBr 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the glycosyl amino acids αGalNAc‐ThrOH ( 4 ) and αLacNAc‐ThrOH ( 6 ), unlike in the case of αGlcN 3 ‐ThrOBn ( 13 ), glycosylation reactions of FmocThr benzyl ester ( 8 ) with the corresponding azido‐derived glycosyl donors αGalN 3 Cl ( 15 ) and αLacN 3 Cl ( 16 )37, 38 afforded exclusively the α isomers αGalN 3 ‐ThrOBn ( 17 , 54 %) and αLacN 3 ‐ThrOBn ( 18 , 60 %), respectively 33. 35 The 1 H NMR spectra of 13 , 17 , and 18 showed characteristic doublet signals for H‐1 with J 1,2 =3.6–3.7 Hz, thus confirming their α configurations.…”
Section: Resultsmentioning
confidence: 99%
“…In a study performed by Sueth-Santiago and collaborators (2017), T. cruzi's specific targets such as trans-sialidases, trypanothione reductase, and cruzipain have been gaining significant interest in the search for molecules against the parasite in the last two decades. In this context, our research group has shown interesting results by putting efforts on synthesizing new structures and by exploring higher selectivity on analogues of existing drugs against T. cruzi (MARCHIORI et al, 2017;ANDRADE et al, 2015;MARTINS-TEIXEIRA et al, 2013). Examples of compounds synthesised by our group against T. cruzi are shown in Figure 2.…”
Section: Drug Discovery and The Search For Specific Targets In T Cruzimentioning
confidence: 99%